Comparison of zootechnical performances, welfare condition and quality traits of hybrid striped bass (Morone chrysops x Morone saxatilis) reared in different Italian farms - Paolo Melotti; Alberto Felici; Leila Forlini; Federico Sirri; Oliviero Mordenti; Adele Meluzzi; Stefano Pignata; Andrea Dees; Alessandra Roncarati (Italian Journal of Animal Science, 2010)
Growth performances of sunshine bass (initial m.b.w.=200±50 g) were examined in 3 different rearing conditions: concrete square basins (HSB-1); raceways (HSB-2); natural ponds (HSB-3). Fish received the same extruded feed (prot. 48.8%; lip. 17.8%). The trial lasted 16 months in HSB-1 and HSB-2 and only 12 months in HSB-3 due to unfavourable welfare status and low growth performances. At harvest (after 16 months), sunshine bass reached a satisfactory mean weight with- out significant differences between groups. HSB-2 fish were longer with a smaller circumference, prob- ably due to different hydrodynamics of the raceway. Glucose, cholesterol, triglycerides, protein, lactic dehydrogenase (LDH), aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), creatine kinase (CK), glycogen of plasma or tissue were not affected by rearing conditions as well as the proximate composition and the fatty acid profile of the fillet.